The influence of the role-playing method and the presentation method on the speaking ability of fifth grade students at SDN 14 Batarang, Maiwa District, Enrekang Regency - Mirna Mirna; Jumiati Jumiati; Aswadi Aswadi (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effect of the role playing and presentation methods on the speaking skills of fifth-grade students at SD Negeri 14 Batarang, Maiwa District, Enrekang Regency. The research used a quantitative approach with a One Group Pretest-Posttest Design. The independent variables in this study are the role playing method (X1) and the presentation method (X2), while the dependent variable is speaking ability (Y). The subjects were 10 students. The instrument used was a speaking skills test administered before and after the treatment. The data were analyzed descriptively and inferentially using normality tests and paired sample t-tests. The results showed a significant improvement in students’ speaking skills after the application of role playing, presentation, and the combination of both methods. The average pretest score of 49.80 increased to 78.70 after role playing, 80.70 after presentation, and 84.00 after the combination. The paired sample t-test revealed a significance value (Sig.) < 0.05 for all treatments, indicating that the differences between pretest and posttest scores were statistically significant. The combination method produced the highest and most consistent improvement in students' speaking performance.It can be concluded that both the role playing and presentation methods, whether applied separately or in combination, have a positive effect on improving students’ speaking abilities. The combined approach is considered the most effective in enhancing students’ confidence, expression, and structured speaking skills.